2016
DOI: 10.1039/c6nj03192g
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and physical properties of 1-methyl-3-(carboxymethyl)benzimidazolium betaine·CuBr2 in crystal and water solution

Abstract: Planar CuO2Br2 complex exists in a triclinic unit cell. Single crystal EPR and MO-theory give electron spin density delocalization parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…UV–Vis absorption spectra of the electrolytes gelled at 35 °C, 45 °C, and 55 °C are shown in Figure S2 . Comparing the electrolytes gelled at 35 and 45 °C, there was a new absorption band caused by d - d transition due to Cu complex observed for the electrolytes gelled at 55 °C [ 40 , 41 , 42 , 43 ]. Thus, it indicated that the chemical bonding states of the electrolytes changed depending on gelation temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UV–Vis absorption spectra of the electrolytes gelled at 35 °C, 45 °C, and 55 °C are shown in Figure S2 . Comparing the electrolytes gelled at 35 and 45 °C, there was a new absorption band caused by d - d transition due to Cu complex observed for the electrolytes gelled at 55 °C [ 40 , 41 , 42 , 43 ]. Thus, it indicated that the chemical bonding states of the electrolytes changed depending on gelation temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the chemical bonding between Cu ions and C=O (NMP) became stronger in the discharged electrolyte. Moreover, the new absorption band caused by d-d transition due to the Cu complex was also observed in the discharged electrolyte according to the UV–Vis spectra [ 40 , 41 , 42 , 43 ]. The Cu complex was formed in the electrolyte of the discharged cell so that the diffusion of the Cu ions is inhibited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S12 in ESI †), which according to the previously reported in the literature for similar compounds. 36,37 All band profile in the spectra is redshifted passing from more donor (L OMe ) to more acceptor (L NO 2 ) ligand in each complex. This is due to polar nature of the ground state, generated by the electronic effect of the ligand over the metal center, and the polar nature of the solvent used in the measurement.…”
Section: Electronic Absorption Spectramentioning
confidence: 99%